Assessment of the performance of nursing staff during the treatment of oxygen for neonates (Journal of Hama University, 2020)
The objective of this descriptive study was to evaluate the performance of the nursing staff during the application of the neonatal oxygen treatment criteria. This study was conducted in the neonatal intensive care unit at Tishreen University Hospital, Obstetrics and Gynecology Hospital in Lattakia, and included all the nurses working in this section where the data showed that the highest percentage of nurses (96.9%) performed well in the procedures prior to initiation of oxygen therapy, and 94.8% performed the exercise, while 54.6% performed in the postoperative procedures. The total performance of the nurses in the treatment of Oxygen was 93.8% with a good level and the lowest 6.2% at the mean level. The study recommended continuous evaluation and conducting educational and training courses for nursing staff on oxygen therapy procedures, conducting similar studies on a larger sample, including medical and nursing staff, and studying the differences between them.